Ciri-ciri dan Jenis Adverbia Pewatas dalam Bahasa Indonesia - Mujid Farihul Amin (Program Studi Sastra Indonesia, Fakultas Ilmu Budaya, Universitas Diponegoro, 2018)
AbstractThe type of borderline adverbs in Indonesian is not just two - as stated in the Indonesian Book Language Book (1993) -, but four. The four types of border adverbs are verb-limiting adverbs, adjective adjuster adverbs, nomina-limiting adverbs, and numerical delimiter adverbs. Although in the discussion we can see a barrier adverb that can be used more than one type, but it will not weaken the description that has been obtained. Keywords: borderline adverbs, Indonesian.IntisariJenis adverbia pewatas dalam bahasa Indonesia bukan hanya dua — seperti dinyatakan dalam Tata Bahasa Buku Bahasa Indonesia (1993) —, melainkan empat. Keempat jenis adverbia pewatas itu adalah adverbia pewatas verba, adverbia pewatas adjektiva, adverbia pewatas nomina, dan adverbia pewatas numeralia. Meskipun dalam pembahasan dapat dilihat adanya adverbia pewatas yang dapat dipakai lebih dari satu jenis, namun hal itu tidak akan melemahkan deskripsi yang telah diperoleh.